Digital Badges in Education - Gibson, David; Ostashewski, Nathaniel; Flintoff, Kim; Grant, Sheryl; Knight, Erin (Springer, 2013)
Digital badges provide new affordances for online educational activities and experiences. When used with points and leaderboards, a badge can become a gamification element allowing learners to compete with themselves or others, and to know how close they are to accomplishing a goal and acquiring its accompanying reputation. In this role, badges motivate continued engagement, which increases time on task and supports skill acquisition through performance. Learning outcomes signified by badges can also be displayed in an e-portfolio or on web sites and are highly transportable to social media sites. In this role they summarize achievement and signal accomplishment. With these characteristics, digital badges have the potential to become an alternative credentialing system, providing visible recognition in digital symbols that link directly via metadata to validating evidence of educational achievements in public displays. This paper will trace the brief history of digital badges, define what they are, give examples of their use, and discuss their educational affordances.